2019
DOI: 10.1097/jcn.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Activity and Cardiorespiratory Fitness Among People Living With Human Immunodeficiency Virus Throughout the Life Span

Abstract: Background: People living with human immunodeficiency virus (PLHIV) are at an increased risk for developing cardiovascular disease (CVD). Physical activity and cardiorespiratory fitness in PLHIV are poorly understood. Objective: The aims of this study were to describe physical activity and cardiorespiratory fitness by sex and age and to examine the association between physical activity and cardiorespiratory fitness in PLHIV, controlling for covariates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…This study was conducted as part of the International Nursing Network for HIV Research's multi-site crosssectional study to describe PA and cardiorespiratory fitness by sex and age in PLHIV (Holzemer 2007;Webel et al 2019b). Consistent with this network's procedural framework, a coordinating site (Case Western Reserve University) finalized the study protocol, developed the standardized training modules, and obtained the primary Institutional Review Board (IRB) approval.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of the International Nursing Network for HIV Research's multi-site crosssectional study to describe PA and cardiorespiratory fitness by sex and age in PLHIV (Holzemer 2007;Webel et al 2019b). Consistent with this network's procedural framework, a coordinating site (Case Western Reserve University) finalized the study protocol, developed the standardized training modules, and obtained the primary Institutional Review Board (IRB) approval.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of physical activity in the pediatrics HIV population is particularly concerning since early implementation promotes healthy habits as adults. In a study with HIV-positive women, those that reported vigorous activity did demonstrate cardiorespiratory fitness improvements [13]. This signifies that the type of exercise, intensity, and duration of physical activity all play a role in reducing the impact of HIV-associated metabolic changes.…”
Section: Physical Activitymentioning
confidence: 97%
“…When applying physical activity to the HIV-positive pediatric population, it is once again important to determine the unique challenges that face them. In general, the HIV population has been found to have not only lower self-reported activity levels, but those who did report were more likely to mention light activity levels [13]. When looking specifically at children with HIV, the majority of children preferred low-impact exercise such as soccer and walking in boys and jogging and walking in girls [24].…”
Section: Physical Activitymentioning
confidence: 98%
See 2 more Smart Citations